Respuesta :

Answer:

f(5) = -2

Step-by-step explanation:

f (x) = -x + 3

Let x = 5

f(5) = -5+3

f(5) = -2

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\text{f(x) = -x + 3}\\\huge\boxed{\rightarrow}\huge\text{ f(x) = -5 + 3}\\\huge\boxed{\rightarrow}\huge\text{ y = -5 + 3}\\\huge\boxed{\rightarrow}\text{ y = -2}\\\\\\\boxed{\boxed{\huge\text{Answer: \bf f(x) = -2}}}\huge\checkmark[/tex]

[tex]\huge\textsf{Good luck on your \& enjoy your day!}[/tex]

~[tex]\huge\boxed{\frak{Amphitrite1040:)}}[/tex]